The Development of Experiental Learning Model To increase the Capacity of Teaching of Universiti Teknologi Malaysia in Semarang Indonesian Schools - Buchori, Achmad; ., Muhdi; Ambarini, Ririn; Widodo, Suwarno; Fadhila, Nur (International Journal of Engineering and Technology, 2018)
In education there is nothing more impressive than direct experience, experiental learning is now getting a place in the process of learning in the classroom, experiental learning is the process of making meaning from the direct experience. Based on the experiential learning model, theÂ prospective teachers ofUniversiti Teknologi Malaysia in cooperation with the Universitas PGRI Semarang help each other to improve their teaching skills by learning from teaching experience in other countries, based on this need, the MOU will be conducted between the two universities.In this research development is done by plomp model with the step that started from the initial assessment, planning, realization / construction, and implementation. With the aim of increasing the capacity of teaching of Universiti Teknologi Malaysia students in vocational high schools in semarang city, eight students taught at SMKN 2 Semarang and SMKN 4 Semarang for 2 months. The sampling technique was taken with random sampling, while data were obtained from questionnaire and interview with students of Universiti Teknologi Malaysia.Based on the questionnaire, it is found that 92% of Universiti Teknologi Malaysia students are very pleased to be able to participate in the international PPL program in Indonesia. This is because their facilities and culture are similar to those in Indonesia, thus facilitating the adaptation process in the schools in Indonesia, while the questionnaire validation of the instructional design experts and learning materials obtained an average of 86% and 90% . It means that modification of experiential learning model is worthy of use in the process of learning in the classroom. The interviews with students shows: 1) 80% of students found difficulties in language terms in Indonesia as they are some terms different from Malaysia so they finally use English when explaining the word that is not understood by students, 2) 90% of UTM students are very happy to teach in schools in Semarang, 3) 90% of students feel the difference of curriculum taught in Indonesia and that inÂ Malaysia so they need adaptation first.Â Â